O judiciário como policymakers, políticas públicas e legitimidade democrática - Alexandre, Edivan Rodrigues (2018)
In the present work, we seek to analyze the study of public policies, their dimensions, related especially to the legitimacy of the Judiciary. It is included in the examined context the phenomenon of the judicialization, its conditions and determining causes, besides the aspect of the construction of policies by the Judiciary. The points examined relate to questions raised about how public policies are decisive for implementing, in the State, the necessary conduction of the realization of social, economic and cultural rights, seen as fundamental rights, using a hypothetical-deductive method, with a comparative and bibliographic study approach. To do so, we seek to show that public policies are instruments used by the powers without distinction, without reserve of exclusivity for a power and prohibition for others. It is also emphasized the political quality of the Judiciary, identifying the three dimensions of public policies, and then analyzing the moment of action of the Judiciary in its capacity as agent of public policies, especially after the implementation of the National Council of Justice . Finally, it is argued about the need for a new vision for the division of powers and its functions, especially aimed at the concreteness of the Social and Democratic State of Law.